Unveiling the potential: iodide-infused nickel-enhanced MXene composite for high-performance sodium ion hybrid capacitors - Nakul Desai; Gurumurthy S C; Shilpa M P; Y N Sudhakar; Vijeth R Shetty; Selvakumar M; Maqsood R Waikar; Rajendra G Sonkawade (Materials Research Express)
2D-MXenes have gained much popularity for energy storage applications such as hybrid capacitors, and they have shown very competitive performance, especially as electrode materials for sodium ion hybrid capacitors. However, they suffer from various problems, such as morphology distortion and fast capacity fading, which results in the poor performance of the battery. As a result, researchers have focused more on MXene-based composite materials to address these issues. In this work, we report a sodium iodide and nickel-decorated MXene-based composite (Ti _2 C/Ni/NaI) material as an electrode for a sodium ion hybrid capacitor. Ti _2 C MXene and Ni were able to provide physical and mechanical strength, and iodine was able to produce redox activity. The composite had a rough surface with readily aggregated 2D-MXene sheets and was uniformly covered with Ni, Na, and I atoms. Several vibrational bands and peaks associated with Ti, Ni, Na, C and O in the Raman while XPS spectra confirmed the effective incorporation of dopants into the MXene sheets and successful synthesis of the Ti _2 C/Ni/NaI composite. The fabricated hybrid capacitor exhibited good capacity retention of 59% after 10,000 cycles at a current density of 0.5 mA g ^−1 ; thus, the Ti _2 C/Ni/NaI composite can be a promising electrode material for sodium-based hybrid capacitors.